ANALYSIS THE IMPLEMENTATION OF ZAMBAK MODULAR SYSTEM IN PHYSICAL AND CHEMICAL CHANGES AND THE EVIDENCE OF CHEMICAL REACTION CONCEPTS IN ONE OF BILINGUAL SCHOOL IN BANDUNG - Rahayu, Neneng Sri (2013)
Purpose of this research study was to analyze the implementation of zambak modular system in physical and chemical changes and the evidence of chemical reaction concepts in one of bilingual school in Bandung. This research study was conducted in one of bilingual school that use special module in the teaching and learning process. Zambak modular system is an unique module because this module provide many things that needed in the teaching and learning process. To make the research study success, the method that appropriate used in data processing is qualitative descriptive research. Qualitative descriptive research is used to analyze the phenomenon in a condition with natural setting. This research was conducted in 8th grade students of junior high school. The researchers try to find out all of the implementation of zambak modular system in teaching and learning process. The triangulation data make the data collection accurately. The result of this research is the implementation of zambak modular system are describe in two ways, firstly is describe by content organization and the secondly describe by learning cycle. The result of the content organization and the learning cycle was the implementation of zambak modular system in the physical and chemical changes and the evidence of chemical reaction concepts were systematically and the pattern of learning cycle was consist of three phase are exploration, concept development, and concept application phase. The using of content organization and learning cycle can endorse the implementation of zambak modular system organize well. In this research, the researcher tries to develop the implementation of module for junior high school. So, the future could be a consideration to improve short comings of the existing module presence. Keywords: Zambak modular system, qualitative descriptive, content organization, learning cycle. Secara umum penelitian ini bertujuan untuk menganalisis implementasi dari zambak modular system di dalam topic perubahan fisika dan kimia serta dalam topic pembuktian reaksi kimia di salah satu sekolah bilingual di Bandung. Zambak modular system merupakan modul yang sangat unik karena modul ini menyediakan beberapa kebutuhan yang dibutuhkan dalam proses belajar mengajar. Metode yang digunakan di dalam penelitian ini adala qualitatif deskriptif. Qualitatif deskriptif digunakan untuk menganalisis fenomena yang terjadi dalam keaadan asli tanpa interfensi dari peneliti. Penelitian ini dilakukan terhadap siswa smp kelas 8. Di dalam skripsi ini, peneliti mencoba untuk mencari tahu bagaiman implementasi dari zambak modular system dalam proses belajar mengajar di salah satu sekolah bilingual di Bandung. Dalam proses pengolahan data dilakukan proses data triangulasi untuk membuat data yang diteliti lebih akurat. Hasil dari penelitian ini adalah implementasi dari zambak modular system digambarkan dalam dua cara yaitu pertama dengan menggunakan content organization dan kedua dengan menggunakan learning cycle. Hasil dari content organization dan learning cycle adalah implementasi dari zambak modular system dalam topik perubahan fisiska dan kimia serta dalam topi pembuktian reaksi kimia adalah sistematik yakni digunakan untuk membantu seluruh bagian proses belajar mengajar dan dimulai dari bagian materi yang mudah hingga komplex sedangkan pola learning cycle terdiri tiga fase yaitu fasde explorasi, pengembangan konsep, dan fase aplikasi. Penggunaan content organization dan learning cycle dapat membantu implementasi dari zambak modular system berjalan dengan baik. Dalam penelitian ini, peneliti mencoba untuk mengembangkan implementasi dari zambak modular system untuk smp, supaya dapat meningkatkan kemampuan siswa smp di masa yang akan datang. Kata kunci: Zambak modular system, qualitative descriptive, content organization, learning cycle.